Long term outcomes of a coordinate care program in patients after myocardial infarction (KOS-MI). (14th October 2021) - Buszman, P P; Kolarczyk-Haczyk, A; Konopko, M; Mazur, M; Przybyla, P; Ciesielska, K; Pietrzyk, E; Hermasch, M; Zurakowski, A; Gasior, M; Rogala, M; Jankowski, P; et al.
Abstract: Introduction: Despite significant progress in treatment of myocardial infarction (MI), the annual mortality remains a challenge. Since 2017, The Coordinated Care in Myocardial Infarction Program (KOS-MI) has been introduced in Poland, which guarantees and coordinates patients to achieve complete revascularization, electrotherapy when necessary, cardiac rehabilitation and access to cardiologist for patients after MI. Purpose: The aim of this study was to assess long term outcomes (3-year follow-up) of patients enrolled in KOS-MI. Methods: This is a prospective multicenter registry of 1973 consecutive patients with myocardial infarction hospitalized in 4 centers of American Heart of Poland from 11.2017 to 11.2018. Patients which constituted a study group were enrolled in KOS-MI program at discharge. A control group consisted patients who received standard of care. Propensity score matching was utilized for patients baseline characteristic matching and results adjustment. Follow-up was obtained from the National Health Fund registry citizens. Combine endpoint of MACCE consisted of death, MI, stroke and repeated revascularization. Results: In total 753 patients were enrolled in KOS program and 1173 constituted a control group. More than 90% of patients in both groups underwent PCI. Patients in KOS-MI were mostly men (70% vs. 65%; p<0, 05), were younger (65 vs. 68; p<0, 05), admitted with STEMI (44, 8% vs. 37, 5%; p<0, 05) with previous history of heart failure (23% vs. 17%; p<0, 05). Patients in the control group had more comorbidities: chronic kidney disease (9, 8% vs. 4, 4%; p<0, 05), previous AMI (17, 6% vs. 12, 6%; p<0, 05), prior PCI (15, 7% vs. 11%; p<0, 05) and atrial fibrillation (11, 7% vs. 8, 4%; p<0, 05). They were more often admitted with NSTEMI (62, 5% vs. 55, 3%; p<0, 05) and acute heart failure (4, 7% vs. 2, 7%; p<0, 05). KOS patients had more often completed revascularization performed (50% vs. 33, 4%; p<0, 05). Following propensity score matching 576 pairs were matched, and patient baseline characteristic were well balanced in all variables. In long- term follow-up (mean 2, 8±0, 27 years) mortality was significantly lower in KOS group (9% vs. 16, 3%; p<0, 05) and MI similar (10, 8% vs. 13, 1%; p=0, 14). MACCE was higher in the control group (43% vs. 30, 2%; p<0, 05). Prevalence of hospitalization for HF and repeated revascularization was higher in the control group (14, 7% vs. 9, 4%; p<0, 05 and 27, 9% vs. 21%; p<0, 05, respectively). After adjustment MACCE remained significantly lower for KOS-MI, whereas there was tendency for lower mortality, hospitalization for HF and repeated revascularizations (Figure 1). Conclusions: Combination and coordination of unrestricted rehabilitation, complete revascularization, electrotherapy and ambulatory cardiologist care in the KOS-MI program improves long term prognosis in patients after MI. FUNDunding Acknowledgement: Type of funding sources: None.